Dasar Penemuan Hukum Hakim Pengadilan Agama Yogyakarta Dalam Mengabulkan Dispensasi Izin Kawin Anak di Bawah Umur Pasca Berlakunya Undang-Undang Nomor 16 Tahun 2019 Tentang Perkawinan (Studi Tentang Legal Reasoning) - Indra Dwi Cristianto; Abdul Jamil (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
This study aims to analyse the basis for the Yogyakarta Religious Court Judges in making legal reasoning in granting dispensations for permission to underage marriage and find out the tendency of Yogyakarta Religious Court Judges to grant dispensations for underage marriage. The problem this research is what is the basis for the Yogyakarta Religious Court Judges in making legal reasoning in granting dispensations for underage marriage after the enctment of Law Number 16 of 2019, and why the Yogyakarta Religious Court Judges tend to grant dispensatons for marriage. This Research uses empirical legal research with an empirical and sociological approach. The data source of this research uses primary data through interviews and secondary data through library studies, document studies, and analysis qualitative. The results of this study indicate that the considerations of Yogyakarta Religious Court Judges in making legal reasoning are more likely to protecting children, but never consider how its relates to divorce data. The reason for the tendency of Yogyakarta Religious Court Judges to grant marriage dispensations is that only consider pity, only take one aspect of the maqasid sharia elements, namely the benefit of protecting children.